Understanding Students' Cognitive Processes: A Qualitative Study of the Influence of Culture-Based Comics on Analytical Skills in Thermodynamics - Erlangga, Sony Yunior; Setyawan, Dhimas Nur; Wijayanti, Astuti; Poort, Eagle Amadeus; Taher, Tamrin (Alpatih Harapan Semesta, 2025)
This study aims to explore how students’ cognitive processes are formed and developed through their engagement with thermodynamics learning using culturally-based comics. Employing a qualitative case study design, the research involved twelve physics education students who had completed thermodynamics coursework. The learning medium used was the Longbumbung Series, an educational comic that integrates narrative and visual representations of local cultural life with thermal physics concepts. Data were collected through participatory observation, in-depth interviews, and students’ written reflections, and analyzed thematically. The findings indicate that incorporating local culture into comics not only enhances students’ affective engagement but also stimulates higher-order cognitive processes such as conceptual interpretation, scientific inference, and analytical articulation. Culture serves as a representational structure that bridges abstract concepts into contextual and reflective understanding. These findings highlight the importance of strategically integrating local cultural elements into science media and pedagogy design to foster deeper intellectual engagement and transformative learning experiences.